Understanding Volunteer-Led 4-H Programs - Bryan D. Terry (EDIS, 2009)
4-H 6.1, a 5-page fact sheet by Bryan D. Terry, discusses management and education roles of Extension professionals, and elements of volunteer-led 4-H programs. Includes references. Published by the Florida 4-H Program, March 2009.